It's Not What You Make, It's How You Use IT : Measuring the Welfare Benefits of the IT Revolution Across Countries - Bayoumi, Tamim; Haacker, Markus (Washington, D.C. : International Monetary Fund, 2002)
This paper analyzes the welfare benefits from falling relative prices of IT (information technology) goods across a wide range of countries. We find, using two separate methodologies and datasets, that welfare benefits mainly accrue to users of IT, not their producers, because of falling relative prices. This is important, as IT production and use are highly differentiated across countries, and implies that earlier work on how IT production affects real GDP, while useful in calibrating the overall benefits of the IT revolution, are a less valuable way of assessing the distribution of benefits.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet